Pengaruh Store Atmosphere, Kualitas Pelayanan dan Customer Experience Terhadap Kepuasan Konsumen di Bhineka Muda Merdeka Denpasar - Ni Putu Shinta Vishuda Yoga Sasmitha; I Wayan Ruspendi Junaedi; I Gede Agus Mertayasa (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2022)
In order to find out indications of the influence of store atmosphere, service quality, and customer experience on consumer satisfaction at Bhineka Muda Merdeka, a study using a population, namely all consumers from Bhineka Muda Merdeka Denpasar, took a sample of 120 people. Based on these results, it can be concluded that the indication of store atmosphere has a positive and significant impact on customer satisfaction with the results of t-count 3,425 > t-table value 1,7 and a significance value of 0,001 <0,05. Another indication is that the quality of service has a positive and significant impact on consumer satisfaction, with the results of t-count 2,699 > t-table value 1,7 and a significance value of 0,008 <0,05. The last indication is that customer experience has a positive and significant impact on consumer satisfaction, with the results of t-count 2,910 > t-table value 1,7 and a significance value of 0,004 <0,05. Broadly speaking, there are indications simultaneously between store atmosphere, service quality, and customer experience on customer satisfaction of 34,9%.